Heart contractive activity specifics in speed endurance building process - Abzalov, R. R.; Abzalov, N. I.; Valeev, A. M.; Abzalov, R. A.; Abzalova, S. V.; Rusakov, R. A. (Theory and Practice of Physical Culture, 2017)
The study was designed to explore the heart contractive functionality in the speed endurance building process in the differently skilled racing skiers' training system. The heart contractive functionality was tested using tetrapolar chest rheograms during the test practices dominated by the speed and speed endurance building ones. The tests showed that the progress pace of the movement speed building component decreased and the speed endurance increased with the growing physical fitness rates. Variations of the heart rates and stroke volumes tested in the racing skiers' muscular training process were less expressed versus the prior study data. This progress was due to a variety of speed-building practices included in the training process to train the skiers for competitive ski sprints. A high priority is to be given to heart contractive functionality profiling studies in the context of speed- and speed-endurance-building practices in the junior athletes` qualification and training system design initiatives.